Maternal and infant oral health benefits from mothers receiving prenatal total oral rehabilitation: a pilot prospective birth cohort study - Yang, Ruqian; Rashwan, Noha; Al Jallad, Nisreen; Wu, Yan; Lu, Xingyi; Wu, TongTong; Xiao, Jin (Frontiers in Oral Health, 2024)
AimThis study aimed to evaluate the maternal and infant oral health benefits from mothers receiving prenatal total oral rehabilitation (PTOR) before childbirth.MethodsBuilding upon our previous investigation, in which 15 expectant mothers received PTOR before their third trimester, achieving a state of oral health free from disease prior to delivery, we conducted a follow-up study to monitor these mothers and their newborns until they reached 2 years of age. We assessed the impact of PTOR on maternal and infant oral health, the utilization of dental care during the postpartum/early-life period, and the carriage of oral cariogenic microorganisms among mothers and their infants. Control groups consisting of 11 children and 17 mothers who did not undergo PTOR were included for comparative analysis.ResultsPTOR demonstrated a sustained improvement in maternal oral health outcomes by the end of 2 years postpartum, evidenced by a reduction in the Plaque Index and decayed surfaces compared with the control group (p < 0.05). PTOR was also associated with increased perinatal oral health literacy compared with the baseline of the mothers themselves (p < 0.05). In addition, PTOR led to a notable increase in maternal dental care utilization, rising from 26.7% before PTOR to 80% at 1 year postpartum and 70% at 2 years postpartum. Intriguingly, 40% of infants in the PTOR group had their first dental visit before reaching 1 year of age, in contrast to national data from the USA indicating a rate of less than 1%. Furthermore, a decrease in plaque Streptococcus mutans was observed in PTOR mothers 2 years postpartum, compared with both their baseline carriage and that of the control group (p < 0.05). Infants in the PTOR group also had a lower incidence of early childhood caries, with 18% in the PTOR group vs. 27% in the control group, although this difference was not statistically significant due to the small sample size.ConclusionsPTOR is associated with sustained oral health benefits and improves dental care utilization by mothers and their infants. Large-scale clinical trials are warranted to validate these study findings.